Optimization of Phytase Production from Rhodotorula mucilaginosa RG-PK20 Using Agricultural Waste - Seprianto; Utama, C. C. Y.; Melani, V.; Handayani, P.; Sukarman (Tropical Animal Science Journal, 2025)
Some ingredients in poultry feed contain phytic acid, which prevents the absorption of nutrients. Microbial phytase enzymes can help with this problem. However, the phytase-producing gene of the novel yeast Rhodotorula mucilaginosa RG-PK20 has been constrained by the high cost of traditional substrates such as sodium phytate. The aim of this study is to evaluate the production of phytase from R. mucilaginosa RG-PK20 using a phytic acid source (substrate) from agricultural waste, with in vitro testing in poultry feed. The fermentation process was conducted utilizing a substrate-to-medium-to-yeast culture ratio of 1:1:1 v/v/w over a period of four days at various temperatures (25, 28, and 30 °C) and pH levels (3, 4, 5, and 6, with 7 as a control). Glucose and urea supplements were given when the optimal conditions were established by measuring the phytase content and activity. The molecular weight of the phytase was confirmed by SDS-PAGE analysis, and the ability of the enzyme to hydrolyze phytic acid was evaluated in vitro. Corn cobs generated the highest amount of phytase, with a concentration of 25.29 mg/mL and activity of 4.46 U/mL. The in vitro tests revealed an 81% reduction in phytic acid levels in poultry feed. These results demonstrate the potential of phytase derived from R. mucilaginosa RG-PK20 to reduce phytic acid in poultry feed ingredients.